The Costs and Threats of the «Green» Energy Transition - I. I. Sechin (Vestnik MGIMO-Universiteta)
This article explores the challenges facing the modern energy market in the context of the accelerated energy transition. It concludes that neither the objectives nor the preparation for the energy transition have been aligned with the actual needs and demands of humanity. The current goals of the energy transition are ideologically driven and unrealistic, prompting countries and companies to reconsider their previously established timelines for achieving carbon neutrality, while investors are growing increasingly disillusioned with the «green» transition. Despite trillions of dollars in investments, alternative energy sources have failed to replace traditional fuels or ensure reliable energy supply. Concurrently, the demand for electricity will continue to rise with the advancement of artificial intelligence and the expansion of data processing centers.The article highlights that in Europe, the emphasis on the «green» energy transition has led to economic downturns, while in developing countries, the implementation of the energy transition has manifested as «green» neocolonialism, characterized by resource extraction. Lobbying for an accelerated energy transition represents one form of market share competition. Another form includes unlawful sanctions and technological restrictions imposed by the United States on several countries, and the use of the dollar as an economic weapon, which has compelled developing nations to embark on dedollarization processes.The article concludes that energy development must be linked to ensuring energy security, combating poverty, and addressing the interests of the majority. Therefore, hydrocarbons will continue to be a critical component of the energy sector.